Identifikasi Perbedaan Status Emosional Pada Perawat Yang Belum Menikah Dan Setelah Yang Terlibat Dalam Perawatan Covid-19 Di Rumah Sakit - Nurasisa; Lisa Fauzia; Fitri A Sabil (Jurnal Ilmiah Mahasiswa & Penelitian Keperawatan, 2023)
There are so many responsibilities that must be held by nurses, which shows that the nursing profession is very vulnerable to emotional stress during the Covid-19 pandemic because of the heavy workload and pressure, fear and anxiety, helplessness, and ignorance of the disease environment. The purpose of the study was to determine the difference in emotional status of unmarried and post-married nurses who were involved in Covid-19 care at the hospital. The design of this study is comparative with a population of 88 people with a sample of 72 using a proposive sampling technique. The method used in this research is quantitative. The questionnaire used is the DASS-42 questionnaire and analyzed by the Independent Samples t-test. The results of bivariate analysis of depression scale sig 0.062, anxiety scale sig 0.071, and stress scale 0.069. The conclusion in this study was that there was no difference between married and post-married nurses who were involved in Covid-19 care in hospitals.